The evolution of plant phenomics: global insights, trends, and collaborations (2000-2021) - Awada, Lana; Phillips, Peter W. B.; Bodan, Ana Maria (Frontiers in Plant Science, 2024)
The emerging interdisciplinary field of phenomics, which explores the intricate relationship between genomics and the physical environment, is revolutionizing plant breeding by providing a comprehensive understanding of traits from molecular to physiological levels. This study investigates the evolution, geographical distribution, collaborative efforts, and central research hubs in the field of global plant phenomics from 2000 to 2021, using data from patents and scientific publications. Our analysis highlights a surge in research activities and a shift in innovation leadership, notably with China's rise as a major force in patent filings. While the U.S.and EU are at the forefront, contributing to over half of the research findings, China's patent filings have soared, representing nearly 70% of all applications during the 2010-2021 period. The study identifies about 50 global research hubs, mainly in the US (36%), Western Europe (34%), and China (16%), as well as a broadening and shift towards more complex collaborative networks. This shift highlights the scientific community's strategic approach to addressing complex research challenges through interdisciplinary methods.